2015
DOI: 10.1186/s12893-015-0084-3
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal gastrointestinal stromal tumors: clinicopathological characteristics, surgery, and long-term outcome

Abstract: BackgroundDuodenal gastrointestinal stromal tumors (DGIST) are rare, and data on their management is limited. We here report the clinicopathological characteristics, different surgical treatments, and long-term prognosis of DGIST.MethodsData of 74 consecutive patients with DGIST in a single institution from June 2000 to June 2014 were retrospectively analyzed. The overall survival (OS) and recurrence/metastasis-free survival rates of 74 cases were calculated using Kaplan–Meier method.ResultsOut of 74 cases, 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 32 publications
4
33
0
1
Order By: Relevance
“…Lymph node metastasis was found only in 2 of our patients, and liver metastasis was found only in one patient. Our study showed a high proportion of low-mitotic-rate tumors (≤5/50 high-power field; 63.3%); this result agreed with that of a previous report [18].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Lymph node metastasis was found only in 2 of our patients, and liver metastasis was found only in one patient. Our study showed a high proportion of low-mitotic-rate tumors (≤5/50 high-power field; 63.3%); this result agreed with that of a previous report [18].…”
Section: Discussionsupporting
confidence: 83%
“…Among all of our patients with duodenal GISTs, the 5-year OS and PFS rates for those with duodenal adenocarcinoma were 89.1 and 72.9%, respectively, which is consistent with previous reports [18,37]. However, in the DOI: 10.1159/000488008…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In multivariate analysis, only the mitotic count was an independent risk factor for adverse prognosis. DGIST is a tumor with favorable prognosis after radical resection, which is similar to other institutions [29]. Long-term follow-up should be recommended for patients with DGIST.…”
Section: Discussionmentioning
confidence: 99%
“…Most dGISTs develop in the second (59-63%) and third portion (22%) of duodenum (55,106), whereas the first and forth are less frequently affected. GIST of ampulla Vateri is extremely rare and according to the review of Kobayashi et al only 12 cases have been described till 2014 (30).…”
Section: Localizationmentioning
confidence: 99%